Analysis of Lao's Interests toward Kumning-Viantiane High-Speed Railway Project with China - Emil Dariskiyah; Haryo Prasodjo; Hafid Adim Pradana (Global Local Interactions: Journal of International Relations, 2022)
This paper talks about an analysis of Lao's interest in working with China on the High-Speed Railway (HSR) project between Kumning, China, and Viantiane, Lao. Using a method called "foreign policy analysis," this paper looks at four factors that Lao considers when deciding whether or not to work with China. The first is that Lao is close to China and has a similar climate. Second, China's strength in the economy. Third, the stability of China's political system. Fourth, China's population, which has to do with the tourism industry and improving Lao' human resources. The authors of this paper say that the results show that a number of indicators make it possible for Lao to connect to the rest of the world through the HSR project, make more contributions to the region, and become more competitive on both the regional and international levels.